Whole exome sequencing and functional characterization increase diagnostic yield in siblings with a 46, XY difference of sexual development (DSD). Issue 212 (September 2021) - Luna, Sofia E.; Wegner, Daniel J.; Gale, Sarah; Yang, Ping; Hollander, Abby; St. Dennis-Feezle, Lori; Nabhan, Zeina M.; Ory, Daniel S.; Cole, F. Sessions; Wambach, Jennifer A.
Highlights: Pathogenic biallelic variants in HSD17B3 are rare and result in 17β-HSD3 deficiency with variable disruption of testosterone production. There is considerable phenotypic diversity among 46, XY individuals with differences of sexual development (DSD). Results from hormone stimulation tests may be non-diagnostic among individuals with DSD resulting from HSD17B3 deficiency. Trio whole exome sequencing (WES) of 46, XY individuals with DSD can increase diagnostic yield. Abstract: Pathogenic biallelic variants in HSD17B3 result in 17β-hydroxysteroid dehydrogenase 3 (17β-HSD3) deficiency, variable disruption of testosterone production, and phenotypic diversity among 46, XY individuals with differences of sexual development (DSDs). We performed quad whole exome sequencing (WES) on two male siblings with microphallus, perineal hypospadias, and bifid scrotum and their unaffected parents. Both male siblings were compound heterozygous for a rare pathogenic HSD17B3 variant (c.239 G > A, p.R80Q) previously identified among individuals with 17β-HSD3 deficiency and a HSD17B3 variant (c.641A > G, p.E214 G) of uncertain significance. Following WES, the siblings underwent hCG stimulation testing with measurement of testosterone, androstenedione, and dihydrotestosterone which was non-diagnostic. To confirm pathogenicity of the HSD17B3 variants, we performed transient transfection of HEK-293 cells and measured conversion of radiolabeled androstenedione to testosterone. Both HSD17B3 variants decreased conversion of radiolabeled androstenedione to testosterone. As pathogenic HSD17B3 variants are rare causes of 46, XY DSD and hCG stimulation testing may not be diagnostic for 17β-HSD3 deficiency, WES in 46, XY individuals with DSDs can increase diagnostic yield and identify genomic variants for functional characterization of disruption of testosterone production.